A geometrical parameter study of the analytical stress calculation in adhesive joints with thick bonding layers. Issue 1 (24th March 2023) - Methfessel, Thomas S.; Becker, Wilfried
Abstract: Strength and failure analyses are critical to the safe and sustainable design of any structure. In the case of adhesively bonded joints, particular attention must be paid to the adhesive layer, which is comparably compliant and subject to high stresses. Determining the stresses in the adhesive layer is essential to identify critical areas in the joint and prevent the formation of cracks. In most applications, bonded joints have thin adhesive layers that can already be accounted for with highly simplified analytical models. However, for the consideration of thicker adhesive layers, advanced models are required that take the adhesive layer into account in more detail. Therefore, in this work, an analytical model with a higher‐order displacement approach is presented to account for more complex deformation behavior in the adhesive layer. The applied advanced displacement approach is particularly suitable for joints with thicker adhesive layers. In addition, the model enables the calculation of stresses and strains in bonded joints for a wide range of joint configurations and applications. A parameter study is carried out to evaluate the effect of different thicknesses of the adhesive layer and to show the advantages of the current model compared to other existing ones. For verification, all analytical results were compared with corresponding Finite Element Analyses.